Comparative evaluation of two university distance learning programmes in south-west Nigeria (2012)
"The challenges of ever-increasing demand for university education in the face of inadequate human and infrastructural resources and rapidly increasing population have necessitated distance learning programmes. This study evaluated Universities of Ibadan and Lagos Distance Learning Programmes. Samples of 200 participants (100 graduates. and 100 employers) were purposively selected. Two research questions guided the research. Two validated instruments with reliability coefficients of 0.82 and O.86 respectively, were used to collect data. Data were analysed using chi square and independent t-test. Findings revealed that graduates of UIDLC performed significantly better than their ULDLI counterparts, in terms of class of degree obtained: a chi-square value of (1632.18) which is significant at 0.05, (p < 0.05). This shows that there is a statistical significant difference in the performance of UIDLC distance learning education graduates and their ULDLI counterparts and it is to the advantage of UIDLC . In addition, graduates of both programmes were making similar positive impact in their work environment as the difference in their job performance is not statistically significant. The two distance learning institutions strove to achieve the objectives of providing quality education through distance learning mode of instruction in educating distance learners to enhance learner's productivity.Recommendations made were: the two institutions must aim at improving teachinglearning resources, learner-support services and establishing human resource development centres to aid develop strong and holistic human resources in order to improve quality of their graduates and also position distance education in Nigeria for international recognition."